Data cultures of mobile dating and hook-up apps: Emerging issues for critical social science research. Issue 2 (July 2017) - Albury, Kath; Burgess, Jean; Light, Ben; Race, Kane; Wilken, Rowan
The ethical and social implications of data mining, algorithmic curation and automation in the context of social media have been of heightened concern for a range of researchers with interests in digital media in recent years, with particular concerns about privacy arising in the context of mobile and locative media. Despite their wide adoption and economic importance, mobile dating apps have received little scholarly attention from this perspective – but they are intense sites of data generation, algorithmic processing, and cross-platform data-sharing; bound up with competing cultures of production, exploitation and use. In this paper, we describe the ways various forms of data are incorporated into, and emerge from, hook-up apps' business logics, socio-technical arrangements, and cultures of use to produce multiple and intersecting data cultures . We propose a multi-layered research agenda for critical and empirical inquiry into this field, and suggest appropriate conceptual and methodological frameworks for exploring the social and political challenges of data cultures.